Comparative Analysis of the Implementation of Religious Moderation as an Effort to Build a Tolerant Culture at Tamansiswa Sukadamai Vocational School and Era Ibang Junior High School - Fahrur Rozy; Azyana Alda Sirait; Indah Widya Jaya Putri Nasution; Mohammad Al Farabi; Ahmad Darlis (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2024)
Religious moderation is defined as a religious attitude that is not extreme, either in the form of radicalism or liberalism, and prioritizes balance and mutual respect. This study aims to analyze the process of internalizing religious moderation as an effort to build a tolerant culture at SMK Tamansiswa Sukadamai. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation from the school, teachers, and students. The study results indicate that the internalization of religious moderation at SMK Tamansiswa Sukadamai is carried out through integrating moderation values ​​in the curriculum, extracurricular activities, and student character development. The school provides an understanding of the importance of tolerance, respecting differences, and avoiding extreme attitudes through an interfaith dialogue approach and activities encouraging cooperation between religious communities.